Artificial intelligence, big data and data science in statistics challenges and solutions in environmetrics, the natural sciences and technology - Steland, Ansgar; Kwok-Leung Tsui
This book discusses the interplay between statistics, data science, machine learning and artificial intelligence, with a focus on environmental science, the natural sciences, and technology.